Presentation of Sudden Death in Emergency Department of a Tertiary Care Hospital of Bangladesh: A Retrospective Study (Bangladesh Critical Care Journal, 2015)
Background: The incidence and causes of sudden death vary in different societies, and these differences are influenced by demographic and clinical factors such as age, gender, risk factors, past medical history and presumed cause of death. This three years long retrospective study describes the influence of these factors on death from sudden cardiopulmonary arrest.Materials and Methods: This is a retrospective study of sudden death among all the age groups who were seen at Emergency Room (ER) of Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh. Total 414 cases of death were reported between 1stJanuary, 2012 to 31st December, 2014. They were investigated retrospectively and subsequently analyzed on age, sex, risk factors, past medical history, endo-tracheal intubation with resuscitation and cause of death. The statistical analysis was performed as appropriate to illustrate any possible association between different demographic variables and cardiopulmonary arrest.Results: Out of 414 deaths, 72.5% were male, & 27.5% were female. The mean age of subjects was 60.60 ± 13.34 years with male mean age of 60.35 ± 13.62 years and female mean age of 59.70 ± 13.24 years. There were three different age groups in this study. 52 deaths were in 17-45 years of age group, 233 death patients were in 46-65 years age group & 129 deaths were more than 65 years age group. Among 46-65years age group 161 deaths were presumed to be due to cardiac cause which is higher than the other two groups. 75.12% of all the study patients had hypertension, 84.06% had diabetes mellitus, 23.43% had CKD & 69.32% had dyslipidaemia. 31.40% patients were active smoker, & 20.53% had prior h/o smoking. Patients who suffered cardiac cause of death had significant history of hypertension (p